The Influence Of Motivation, Organizational Communication And Job Satisfaction On The Performance Of Employees In Executive Travel Services Companies - Rulyenzi Rasyid; Dian Ariani; H. M. Anwar; Muhammad Syafri; Muhammad Irvan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study was carried out at one of Jakarta's transportation businesses. In this study, the dependent variable is employee performance, while the independent factors are organizational communication and motivation, the intervening variables are work satisfaction, and the intervening variables are intervening variables. Through the use of intervening factors, this study tries to ascertain the interaction between the independent variables and the dependent variable both concurrently and partially directly or indirectly. Using a basic random sampling procedure, 100 respondents made up the sample size. The route analysis approach, which is based on prior correlation and regression analysis, is used to evaluate hypotheses. The outcomes of a hypothesis test conducted on the model-1 structure demonstrate that organizational communication, motivation, and work satisfaction all concurrently have a beneficial impact on employee performance. The outcomes of a hypothesis test conducted on the model-2 structure demonstrate that organizational communication and motivational factors both positively impact work satisfaction.